Flying with two wings or coming of age of copyrightisation? a historical and socio-legal analysis of copyright and business model developments in the Chinese music industry - Chen, Zhen Troy (2021)
Following the third copyright law amendment in China, this paper offers a timely contribution to the debates on the shifting policy, governance and industry landscape of the Chinese music industry. This paper conducts a historical and socio-legal analysis of the development of Chinese copyright law with regards to the music industry and argues that the Chinese digital music industry has developed to a stage where three business models collide, namely the cultural adaptation model, the renegade model and the platform ecosystem model. This paper draws on interdisciplinary literature and discourses from legal studies, business studies and cultural studies and provide new evidence of the much neglected autonomous development of Chinese copyright law on top of foreign pressure and the desired reforms to further integrate into the global market economy.